Human serum albumin hydropersulfide is a potent reactive oxygen species scavenger in oxidative stress conditions such as chronic kidney disease - Shibata, A.; Ishima, Y.; Ikeda, M.; Sato, H.; Imafuku, T.; Chuang, Victor; Ouchi, Y.; Abe, T.; Watanabe, H.; Ishida, T.; Otagiri, M.; Maruyama, T. (Academic Press, 2016)
Recently, hydropersulfide (RSSH) was found to exist in mammalian tissues and fluids. Cysteine hydropersulfide can be found in free cysteine residues as well as in proteins, and it has potent antioxidative activity. Human serum albumin (HSA) is the most abundant protein in mammalian serum. HSA possesses a free thiol group in Cys-34 that could be a site for hydropersulfide formation. HSA hydropersulfide of high purity as a positive control was prepared by treatment of HSA with Na2S. The presence of HSA hydropersulfide was confirmed by spectroscopy and ESI-TOFMS analysis where molecular weights of HSA hydropersulfide by increments of approximately 32 Da (Sulfur atom) were detected. The fluorescent probe results showed that Alexa Fluor 680 conjugated maleimide (Red-Mal) was a suitable assay and bromotrimethylammoniumbimane bromide appeared to be a selective reagent for hydropersulfide. The effect of oxidative stress related disease on the existence of albumin hydropersulfides was examined in rat 5/6 nephrectomy model of chronic kidney disease (CKD). Interestingly, the level of hydropersulfides in rat 5/6 nephrectomy model serum was decreased by a uremic toxin that increases oxidative stress in rat 5/6 nephrectomy model. Furthermore, we demonstrated that the levels of HSA hydropersulfide in human subjects were reduced in CKD but restored by hemodialysis using Red-Mal assay. We conclude that HSA hydropersulfide could potentially play an important role in biological anti-oxidative defense, and it is a promising diagnostic and therapeutic marker of oxidative diseases.